TRAINING TECHNOLOGY TO OVERCOME ADAPTATION BARRIERS - Elena K. Klimova; Olga A. Pomazina (Высшее образование в России)
The authors dwell on training technology aimed at overcoming adaptation barriers by first-year students. Specially organized training promotes development of educational professional activity, development of students’ self-understanding. The article describes the main barriers arising during the period of adaptation of first-year students to educational professional activity. Among them are: the low level of self-understanding, fear of entry into a new group, unformed professional intentions, the low level of self-checking, lack of skills of constructive interaction. Stages of training adaptation work on overcoming of these barriers are given. The results of assessment the efficiency of the training technology are presented. Students who have completed the course of social and psychological adaptation increase their level of self-understanding, internal motivation to educational professional activity, self-checking, self-control, self-management, constructive interaction. Thus, the adaptation training is an effective technology to overcome the barriers to development of educational professional activity, self-understanding and effective communication by first-year students.